Utilization of Artificial Intelligence Tools by Final Year Chemistry Students in Tertiary Institutions in Owerri, Imo State, Nigeria - Okore, Glory Jerry; Ehirim, Appolinus; Nwaodu, Mary-Claret; Okeke, Pamela; Metu, Sharon Ifechi (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
This study delves into the utilization of artificial intelligence (AI) tools among final-year chemistry students in tertiary institutions in Owerri, Imo State. With AI revolutionizing various sectors, its integration into chemistry research offers unprecedented opportunities. However, concerns persist regarding students' proficiency and familiarity with AI tools, potentially impacting research outcomes. Through a cross-sectional survey design, data was collected from 50 chemistry students across four institutions, which represents 30% of the entire chemistry student population. Results indicate widespread use of AI tools for data analysis, modelling chemical reactions, literature review, molecular visualization, and simulation, aligning with contemporary research trends. Additionally, students exhibit familiarity with AI tools, having received adequate training and possessing confidence in their usage. Institutions provide varied access to AI tools, fostering collaboration and meeting students' research needs. Despite perceived benefits such as improved research accuracy and productivity, challenges including technical issues and cost barriers persist. Nonetheless, AI tools enhance students' understanding of complex chemical concepts. This study underscores the crucial importance of AI in reinforcing modern chemistry research and highlights the need for continued integration and support within educational settings.